2017
DOI: 10.1016/j.smrv.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect and sleep: A systematic review

Abstract: A sizeable literature has implicated sleep in the phenomenological experience of various mood disorders, vulnerability to psychopathology, and overall poor psychological functioning. By contrast, positive affective states (e.g., joy, happiness, vigor, positive mood) that may contribute to sleep have been understudied. This systematic review integrates findings from cross-sectional, longitudinal, ambulatory, and experimental studies that investigate the association between positive affect and sleep. A comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
81
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 86 publications
11
81
1
3
Order By: Relevance
“…The association of positive affects, subjective well-being, and optimism with less sleep disturbances is reported in other studies. Ong et al 13 , in a meta-analysis, although evaluating only few valid studies, have found consistency of association between positive affects and better sleep. In a cross-sectional analysis, authors have found a moderate correlation between sleep quality with mood and optimism 16 , as well as an inverse association between positive affects and hedonic well-being and sleep problems 15 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The association of positive affects, subjective well-being, and optimism with less sleep disturbances is reported in other studies. Ong et al 13 , in a meta-analysis, although evaluating only few valid studies, have found consistency of association between positive affects and better sleep. In a cross-sectional analysis, authors have found a moderate correlation between sleep quality with mood and optimism 16 , as well as an inverse association between positive affects and hedonic well-being and sleep problems 15 .…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown associations of states of affect, such as happiness, positive feelings, and vitality, with sleep quality 13 and sleep duration 14 . There seems to be a bidirectional association between well-being and sleep: on the one hand, sleep disturbances negatively affect well-being and positive affects and, on the other hand, the better state of well-being promotes a better sleep quality 13 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sleep of good quality and sufficient duration is assumed to benefit health and brain function ( 1 ). Epidemiological studies indicate that both extreme short and extreme long self-reported sleep durations are negatively associated with cognitive function and mood ( 2 5 ). In interventional studies, acute and chronic sleep deprivation ( 6 , 7 ), and disruption of both Slow Wave Sleep (SWS) and sleep continuity ( 8 , 9 ) all lead to an increase in daytime sleepiness, a reduction in subjective sleep quality as well as a reduction in sustained attention and processing speed.…”
Section: Introductionmentioning
confidence: 99%
“…A positive mood may influence sleep by modifying the effects of stress (Ong et al, 2016) and increasing activity in neural regions in the brain that assign meaning and value, motivation, and attention (Young and Nusslock, 2016). In parents, positive mood is strongly related to supportive parenting whereas negative mood is related to negative parental behavior (Rueger et al, 2011).…”
Section: Moodmentioning
confidence: 99%